High preseason temperature variability drives convergence of xylem phenology in the Northern Hemisphere conifers - Zhang, Yaling; Huang, Jian-Guo; Wang, Minhuang; Wang, Wenjin; Deslauriers, Annie; Fonti, Patrick; Liang, Eryuan; Mäkinen, Harri; Oberhuber, Walter; Rathgeber, Cyrille B K; Tognetti, Roberto; Treml, Václav; et al. (Current biology, 2024)
Wood growth is key to understanding the feedback of forest ecosystems to the ongoing climate warming. An increase in spatial synchrony (i.e., coincident changes in distant populations) of spring phenology is one of the most prominent climate responses of forest trees. However, whether temperature variability contributes to an increase in the spatial synchrony of spring phenology and its underlying mechanisms remains largely unknown. Here, we analyzed an extensive dataset of xylem phenology observations of 20 conifer species from 75 sites over the Northern Hemisphere. Along the gradient of increase in temperature variability in the 75 sites, we observed a convergence in the onset of cell enlargement roughly toward the 5th of June, with a convergence in the onset of cell wall thickening toward the summer solstice. The increase in rainfall since the 5th of June is favorable for cell division and expansion, and as the most hours of sunlight are received around the summer solstice, it allows the optimization of carbon assimilation for cell wall thickening. Hence, the convergences can be considered as the result of matching xylem phenological activities to favorable conditions in regions with high temperature variability. Yet, forest trees relying on such consistent seasonal cues for xylem growth could constrain their ability to respond to climate warming, with consequences for the potential growing season length and, ultimately, forest productivity and survival in the future.
Keywords: stromy; Temperature; Climate Change; Ecosystem; cévnaté rostliny; 5(th) of June; Trees; Xylem; xylém; winter chilling; cell differentiation; roční období; Seasons; wood formation; ekosystém; klimatické změny; Northern Hemisphere; teplota; spring forcing; Tracheophyta